The Indies viceroys of the Hispanic Monarchy: A historiographical review - Gálvez Martín, Rubén (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
This text offers a historiographical overview of the different lines of research that have addressed the figure of the viceroys of the New World of the Hispanic Monarchy. Consequently, it reveals the most significant perspectives and contributions, beside the deficiencies found, in addition to the enormous and suggestive possibilities that the figure of the Indies Viceroys, both complex and multifaceted, treasures. A balance that, in the same way, does not ignore the historiographical tradition that this real agent has aroused in other territories. This article considers the current trends in historical analysis, due to the academic view on the vicesoberanos has been closely linked to the rhythms and studies of general historiography, and of Hispanic modernist historical literature, in particular.